Tathwîr Al-Mawâd Al-Ta’lîmiyah li Mahârah al-Istimâ’ al-Mustamidah min as-Saqâfah al-Mahalliyah ladâ Tholibât al-Jâmi’ah - Rosyad; M. Baihaqi; Muhammad Afthon Ulin Nuha (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Purpose- This study aims to develop teaching materials for listening skills based on local content, determine the level of validity of teaching materials, and measure the level of effectiveness of the developed teaching materials.  Design/Methodology/Approach- This study uses research and development methods based on the Borg and Gall model with special treatment from researchers. Sources of data from students, expert councils, and policy makers in Islamic boarding schools were obtained through observation, interviews, and tests. The data will then be analyzed qualitatively and quantitatively simultaneously with interactive analysis and t-test. The subjects of this study were all female students of the intensive Arabic language program who were determined through a purposive technique, with a total of 25 samples.  Findings- Among the results of this study were the results of the pre-test reaching 1882 with a rate of 75.28, while in the post-test it reached 2045 with a rate of 82.16. The effectiveness of the developed material is seen at a score of 12.69 which is greater than the table score at the 2.80 level. Thus teaching materials developed based on local content are effective in improving the listening skills of female students of the intensive Arabic language program. Research Limitation/Implications- The formal finding of this research is that teaching materials that are arranged thematically based on local content can improve Arabic listening skills for students.